Reproducible resistive switching behavior in sputtered CeO(2) polycrystalline films - Lin, Chih-Yang; Lee, Dai-Ying; Wang, Sheng-Yi; Lin, Chun-Chieh; Tseng, Tseung-Yuen (My University, 2008)
Sputter-deposited CeO(2) film in the metal-insulator-metal structure exhibits repeatable resistive switching behavior under voltage sweep. Based on the X-ray diffraction patterns and the cross-sectional scanning electron microscope image, the CeO(2) film is polycrystalline with columnar grains perpendicular to the bottom electrode. Moreover, due to the symmetric device structure of Pt/CeO(2)/Pt, the resistive switching behavior is independent of bias polarity so that both positive and negative voltages can switch the device from high conducting state (ON-state) into low conducting state (OFF-state) and then back to ON-state, which is named non-polar resistive switching. The resistance ratio between two memory states is about five orders of magnitude, which is stable over 10(4) S at 0.3 V stress. in addition, the resistance ratio decreases with increasing the current compliance during forming process. The stability of ON-state, OFF-state, and as-deposited film state (the state before performing forming process) against temperature is also investigated in this study, showing that the OFF-state is less stable. (C) 2008 Elsevier B.V. All rights reserved.